Political Imagination and Utopian Pedagogy - Salmenniemi, Suvi (Taylor & Francis, 2025)
This article contributes to the theorisation of utopian pedagogy by exploring how arts-based exercises can be used in engaged pedagogy to facilitate the cultivation of political imagination. Engaging with theoretical discussions of utopian thought and political imagination, we draw on pedagogical experiments from our sociology course “Exercises in Political Imagination” to pose the following questions: How can arts-based exercises be used in engaged pedagogy to foster political imagination? What kinds of tensions or difficulties does this process involve? What kinds of conceptions of politics and social change do these exercises produce? On the basis of our pedagogical experiments, we suggest that the notion and practice of utopian pedagogy is characterised by the following features: disengagement from—and disinvestment in—the status quo as a means by which to open up imaginative capacities; an approach to politics as something that emerges from the process of exercising imagination and that emphasises complex interconnections between the personal and political; an understanding of imagination as a collective process rather than an individual disposition; and encouragement to embrace a variety of scales for social change, observing both their entanglement and emancipatory potential in everyday life. The article concludes that utopian pedagogy can serve as an important tool of transformative politics by facilitating political imagination and widening the horizon of the possible in the context of the neoliberalisation of higher education.